Wykładnia prawa islamu według hanbalickiej szkoły prawa - Samojedny, Małgorzata (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2014)
The Islamic world, much like Christianity, is not homogeneous. Instead, there are many factions, strands, and conceptions. The most numerous group of Muslims is the Sunni faction, which makes up about 90% of all Muslims. Among them, how-ever, one finds separate strands called schools, which represent various and distinct interpretations of the fundamentals of Islamic law.The Hanbali School of Islamic Law, one of those strands, is worth looking at closer, especially its ideological doctrine, as it offers a perfect example of the process of establishing a new doctrine. In the beginning, the Hanbali School was but a minor concept. However, it has grown to become one of the main ideological movements of the Sunni faction.
Keywords: islam; radykalizm; Ibn Hanbal, Ahmed (780-855); wahhabizm; fundamentalizm